Peran Widyaiswara dalam Mewujudkan Birokrasi yang Berkualitas: Studi Kasus Pusdiklat Manajemen Kementerian Pertahanan - Suharin Zulaikha Harinz (JURNAL PENDIDIKAN DAN PELATIHAN PERTAHANAN, 2024)
Bureaucracy is an important factor in government, and the Ministry of Defense has a program towards world-scale bureaucracy. One of the important factors in organizing training is Widyaiswara. The aim of this research is to describe the important role of Widyaiswara in developing the competency of ASN Ministry of Defense. The research method uses secondary data-based studies based on PKA and PKP activities in 2018-2022. The results of research related to PKA show that Widyaiswara as a material teacher and supervisor is satisfactory, as is the case regarding PKP activities. Participants experience increased leadership competency according to their level. Widyaiswara's empowerment of the PKA and PKP programs is very good, thus supporting the realization of Smart ASN. Widyaiswarwa students still need to improve their competencies, including building mindsets and optimizing digital-based learning technical competencies.